Understanding Implications of Residual Limb Length, Strength, and Range-of-Motion Impairments of Veterans With Upper Limb Amputation. (4th June 2022) - Resnik, Linda; Borgia, Matthew; Cancio, Jill; Heckman, Jeffrey; Highsmith, M. Jason; Levy, Charles; Phillips, Samuel; Webster, Joseph
Abstract : Objective: The aim of the study was to describe and quantify the relationship between limb impairment variables to key functional outcomes. Design: This was an observational study of 107 participants with unilateral above/at-elbow or below-elbow/wrist amputation. Demographics, prosthesis characteristics, residual limb length, and prevalence of passive range-of-motion restrictions, and strength impairments were described. Correlations between impairment variables were estimated. Linear regressions examined associations between impairment variables and activity performance, health-related quality of life, disability, and prosthesis satisfaction. Results: Prevalence of short/very short below- and above-elbow residua was 25.7% and 12.5%, respectively. Shorter below-elbow/wrist residual limb length was correlated with elbow flexion weakness ( r = 0.30) and prevalence of passive range of motion ( r = 0.25). Shoulder prevalence of passive range-of-motion restrictions were correlated with shoulder ( r = 0.27–0.51) and elbow weakness ( r = 0.25–0.46). In regressions, activity performance was worse for those with shoulder flexion prevalence of passive range-of-motion restrictions ( B = −5.0, P = 0.03) and better for those with flexion restrictions ( B = 3.3, P = 0.04) compared with normal prevalence of passive range of motion. Prosthetic satisfaction was lower for those with limited elbow prevalence of passive range of motion. Conclusions: Short below-elbow residual limb length was correlated with impairment of elbow flexion strength and prevalence of passive range of motion. Prevalence of passive range-of-motion restrictions were most prevalent at the shoulder and were strongly correlated with weakness in the same planes of motion. Few significant associations were found between impairment variables and outcomes.